Filsafat Etika Sebagai Dasar Pembentukan Karakter Mahasiswa di Institut K.H Ahmad Sanusi - Neng Rani; Lina Agustina; Rika Oktaviani; Noer Syaqilla (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to describe the implementation of ethical philosophy learning and the assessment pattern for student learning outcomes at the KH. Ahmad Sanusi Sukabumi Institute (INKHAS). Ethical philosophy is understood as a critical study of good and bad values in human actions, which not only accepts moral teachings normatively, but examines them rationally and in depth. In the learning process, this course applies discussion and dialogue methods as the main approach to encourage students to think critically, express opinions argumentatively, and build mutual respect. The lecturer acts as a facilitator who directs the discussion, instills academic ethics, and maintains a scientific learning flow. The assessment pattern does not focus on memorizing theories, but rather on students' analytical abilities as measured through discussion participation, individual assignments, and group assignments. The results of the study indicate that this method is effective in developing students' conceptual understanding, critical thinking skills, and moral awareness, although obstacles such as lack of motivation in some students due to the abstract nature of the material are still found. Overall, ethical philosophy learning at INKHAS plays an important role in shaping ethical character, reflective thinking, and responsible attitudes in academic and social life.